1999
DOI: 10.1002/(sici)1099-0488(19990101)37:1<61::aid-polb6>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport properties for carbazolyl groups pendant poly(glutamate)

Abstract: Carbazolyl groups pendant poly(glutamate) (PCLG) was prepared to analyze its charge‐transport properties by employing mobility measurements and thermally‐stimulated current (TSC) measurements. The mobility induced TSC (MITSC) model proposed by I.Chen was employed to evaluate the experimental TSC spectra with mobility results. Simulated MITSC spectra showed good agreement in its peak temperature with experimental TSC spectra for PCLG. This suggests that the carrier transport followed the trap‐limited mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The PCLG film showed emission peaks assignable to the second and the sandwich excimers. The average intersite distance between carbazole groups along the PCLG chain is about 10 Å and the fluctuation of the intersite distances is affected by the side chain configuration 7. The appearance of the emission from excimer sites is understandable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCLG film showed emission peaks assignable to the second and the sandwich excimers. The average intersite distance between carbazole groups along the PCLG chain is about 10 Å and the fluctuation of the intersite distances is affected by the side chain configuration 7. The appearance of the emission from excimer sites is understandable.…”
Section: Resultsmentioning
confidence: 99%
“…In trap‐limited hopping charge transport mechanism, the mobility (μ) in the film is expressed by using the average intersite distance d as follows:7 where A is a constant, and γ is the wave‐function overlap factor. The average distance between planer carbazolyl groups in a PVK and a PCLG chain was calculated as 6.6 Å and 10 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this field, the carbazolyl group is one of the most widely used chromophores for charge photogeneration and transport and other potential applications. This is why polymers with pendant carbazolyl groups have received so much attention 12–15…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in a LC cell, PCELG has a high mobility of $10 À3 cm 2 /V s. This is higher than those for amorphous PCELG (10 À8 cm 2 /V s) and PVCz films (10 À7 cm 2 /V s) by about 4-5 orders of magnitude. [6][7][8][9] Consequently, highly ordered intra-and interchain structures are considered to improve photoconductivity and charge carrier transport.…”
mentioning
confidence: 99%